2017
DOI: 10.1007/s00228-016-2188-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of the STOPP/START criteria in hip fracture patients

Abstract: PurposeThe aim of this study was to investigate the clinical relevance of potentially inappropriate medications (PIMs), identified by the STOPP criteria, and potential prescribing omissions (PPOs), identified by the START criteria, and to identify predictors for clinically relevant PIMs and PPOs.MethodsThe STOPP and START criteria were applied on the medication lists of 200 older hip fracture patients, consecutively recruited to a randomized controlled study in 2009. For each identified PIM and/or PPO, the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
2
31
1
3
Order By: Relevance
“…Furthermore, the joint expertise of the clinical pharmacologist and the geriatrician in the evaluation of the individual patient records strengthens the evaluations and conclusions in our report. The female preponderance, age, high frequency of comorbidities, widespread use of medications, FRIDs, and PIMs in our patients correspond well to those from other studies of Danish and international cohorts of patients with hip fractures [11,12,[24][25][26]. Thus, our population may be a representative sample of elderly patients with hip fracture.…”
Section: (37)supporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the joint expertise of the clinical pharmacologist and the geriatrician in the evaluation of the individual patient records strengthens the evaluations and conclusions in our report. The female preponderance, age, high frequency of comorbidities, widespread use of medications, FRIDs, and PIMs in our patients correspond well to those from other studies of Danish and international cohorts of patients with hip fractures [11,12,[24][25][26]. Thus, our population may be a representative sample of elderly patients with hip fracture.…”
Section: (37)supporting
confidence: 84%
“…Thus, FRIDs can be regarded as a modifiable risk factor. Furthermore, a recent study showed that 85% of elderly patients with a hip fracture were prescribed potentially inappropriate medications (PIMs), which may be unnecessary or entail a high risk of adverse effects [12]. The Screening Tool of Older Persons' Prescriptions (STOPP) [13] may guide the performance of a medication review, both by pointing out situations in which certain medications are potentially inappropriate and by identifying certain FRIDs as PIMs.…”
Section: Introductionmentioning
confidence: 99%
“…Summarized, drawing conclusions on prescribing quality from our results may be a delicate task, as register data lack important information for individualized treatment decisions. Indeed, indicators of prescribing quality often have limited applicability at the individual patient level [29,30]. Nevertheless, one cannot exclude that undertreatment may exist to some extent, as has previously been suggested [31].…”
Section: Discussionmentioning
confidence: 99%
“…8 Secondly, baseline functionality, based on the Barthel index (total, severe, moderate, slight or no dependence), 15 ambulation (independence/1 stick; walker/2 sticks; high assistance; not walk), 16 Thirdly, surgical features such as surgical intervention, surgical urgency, surgery type (nail, partial bipolar prosthesis, monopolar prosthesis, total prosthesis and screws), 8 ASA scores (II -Moderate Systemic Disease; III -Severe Non-disabling Systemic Disease; IV -Severe Vital-risk Systemic Disease), 18 and non-surgical cause (death, orthopedic care, high surgical risk and hospital transfer), 5 as well as baseline pharmacologic treatments (anti-hypertensives, benzodiazepines, antidepressants, proton-pump inhibitors, antiplatelets, anticoagulants, oral antidiabetic agents, analgesics, antidementia, neuroleptics, anti-osteoporosis, bronchodilators, domiciliary Oxygen, anti-Parkinsonians and Insulin) were determined. 19 Finally, complications (anemia, transfusion, delirium, constipation, renal function alteration, urinary tract infection, infection or respiratory insufficiency, malnutrition, heart failure, acute retention of urine, ischemic heart disease, death, pressure ulcers, seroma, surgical wound infection, ictus, venous thrombosis or thromboembolism), 20 and features at hospital discharge (destination, home move, ambulation and discharge) were observed. 21…”
Section: Procedures Ant Outcomesmentioning
confidence: 99%